Correction: Dibismuthanes in catalysis: from synthesis and characterization to redox behavior towards oxidative cleavage of 1, 2-diols. Issue 22 (26th May 2021) - Magre, Marc; Kuziola, Jennifer; Nöthling, Nils; Cornella, Josep
Abstract : Correction for 'Dibismuthanes in catalysis: from synthesis and characterization to redox behavior towards oxidative cleavage of 1, 2-diols' by Marc Magre et al., Org. Biomol. Chem., 2021, DOI: ; 10.1039/d1ob00367d .